The existence of Malaqbiq Tau Mandar local culture to empower students' educational character - Nurhikma Ramadhana; Mimien Henie Irawati Al Muhdhar; Sulistijiono Sulistijiono (LPMPP Universitas Negeri Yogyakarta, 2023)
Various studies and facts show that a developed nation is a nation whose character is strong. The integration of local wisdom culture is important to be developed into learning materials because it has a high potential to be utilized in developing the character of students. West Sulawesi Province can be one example. Mandar people living in the province have various cultures and philosophies of cultural diversity which are called the